Strategi Pengembangan Sumber Daya Manusia (SDM) Terhadap Produktivitas Kerja Pegawai - kadek marlina dewi; I Gusti Made Oka Astana (ARTHA SATYA DHARMA, 2024)
The results of this research show that motivation has a positive and significant effect on work productivity at the Buleleng Regency Regional Development Planning Agency. With these results it can be said that the higher the motivation of each employee, the more it will help them increase the resulting work productivity. Communication has a positive and significant effect on work productivity at the Regency Regional Development Planning Agency, with these results it can be said that good communication between employees and leaders or fellow employees will have an influence on work productivity. Skills have a positive and significant effect on work productivity at the Buleleng Regency Regional Development Planning Agency, with these results it can be said that each individual's skills at work have an influence on work productivity. The simultaneous significant test results of each research variable used, namely motivation, communication and ability (skill) simultaneously on the influence of work productivity obtained a value from the SPSS application of 11.639 and a significant value of 0.000.